PENGARUH PREPARASI BAHAN BAKU ROSELLA DAN WAKTU PEMASAKAN TERHADAP AKTIVITAS ANTIOKSIDAN SIRUP BUNGA ROSELLA (Hisbiscus sabdariffa L.) - Hartiati, Amna; Mulyani, Sri; Dwi Pusparini, Ni Made (Agrotekno, 2012)
The objectives of this research were to determine effectof rosella preparation and cooking time on antioxidantactivity of rosella syrup. Three repetition of CompletelyBlock Design with two factors of factorial experiment wasused in this research. The first factor was two levels ofrosella preparation namely fresh and dried rosella, and thesecond factor was three levels of cooking time 10, 20, and 30minutes. Testing comprised measurement on the ability oncapturing DPPH free radical, scoring and hedonic tests.The research results indicated that using fresh rosellaimproved the antioxidant activity of rosella syrup and itsvalue was 0.026%, while rosella syrup from dried rosella was0.020%. Until cooking time of 20 minutes, antioxidantactivity of rosella syrup still increased, but longer cookingtime than 20 minutes showed no significant effect.Preparation and cooking time affected significantly on colourof syrup, but not on aroma, taste and the overall acceptance.
Keywords: rosella, syrup, antioxidant activity